The Diffusion of Jaranan Cultural Innovation among Generation Z through Art Studio Activities - Siti Mahfudhotin; Saifuddin Zuhri (Interaction Communication Studies Journal, 2026)
The development of globalization and digital technology has led to a decline in generation Z’s interest in traditional culture, including the traditional jaranan performance art. This condition highlights the need for effective communication strategies to encourage young people to remain interested in and actively participate in cultural preservation. This study aims to identify and analyze the communication strategies employed by the Wahyu Kawedhar Art an Cultural Studio in preserving jaranan culture among generation Z. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. This research informants consisted of the head of the art studio, instructor, and generation Z members. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the communication strategy was implemented through identifying generation Z as the primary target audience, developing educational and persuasive messages, utilizing face to face communication as the primary communication medium, and optimizing the role of communicators who posses credibility and emotional closeness with the members. In addition, the art studio introduced innovations in the presentation of jaranan performances without diminishing their cultural values. Intensive community communication also fostered a sense of kinship, solidarity, and active participation among generation Z members in the studio’s activities. This study concludes that adaptive, participatory, and educational communicarion strategies that adaptive, participatory, and educational communication strategies play a significant role in enhancing generation Z’s involvement and supporting the sustainability of jaranan cultural preservation amid the rapid development of the modern era.